2018
DOI: 10.1136/neurintsurg-2017-013608
|View full text |Cite
|
Sign up to set email alerts
|

LVIS Blue as a low porosity stent and coil adjuvant

Abstract: The LVIS Blue represents a safe option as a coil adjunct for endovascular embolization within both the proximal and distal anterior and posterior circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…In the present study, although immediate angiographic results demonstrated a complete occlusion rate of 59%, progression to total occlusion was impressive with complete obliteration (86.4%) at the 1-year follow-up; morbidity or mortality did not occur. This result showed better angiographic and clinical outcomes than in previous studies on LVIS or LVIS Blue 11,18) .…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In the present study, although immediate angiographic results demonstrated a complete occlusion rate of 59%, progression to total occlusion was impressive with complete obliteration (86.4%) at the 1-year follow-up; morbidity or mortality did not occur. This result showed better angiographic and clinical outcomes than in previous studies on LVIS or LVIS Blue 11,18) .…”
Section: Discussionsupporting
confidence: 49%
“…The LVIS Blue, a new modification of LVIS, is a braided stent that provides a higher degree of metal coverage (approximately 28%) and is increasingly used for SAC. The LVIS Blue showed improved wall apposition and aneurysm neck coverage 11) and has a good crossing profile for microcatheters, better wall apposition and less perforator coverage than a flow redirection endoluminal device (FRED) 14) .…”
Section: Introductionmentioning
confidence: 99%
“…3 ). An explanation is the higher metal coverage (smaller cell size) of the Leo+ Baby compared to other laser-cut and braided MSs—although it is still not comparable to typical FDSs [ 3 , 19 ]. A smaller cell size works as a more effective scaffold for endothelial growth leading to a progressive sealing of the aneurysm neck [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these stents, the low-profile visualized intraluminal support (LVIS) stent (MicroVention, Tustin, California, USA) has the highest metal coverage ratio among commercial intracranial stents. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] As alternatives, flow diverter stents are a more recent and special type of intracranial stent, although the pipeline embolization device (PED) (Medtronic Neurovascular, Irvine, California, USA) is currently one of the most commonly used flow diverter stent in some countries. [15][16][17] Flow diverters significantly reduce the blood flow into aneurysms by "flow diversion," resulting in aneurysmal thrombosis.…”
Section: Introductionmentioning
confidence: 99%